2014
DOI: 10.1007/s10803-014-2174-y
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of Autism and Asthma in a Nationally-Representative Sample of Children in the United States

Abstract: Few large epidemiological studies have examined the co-occurrence of autism and asthma. We performed a cross-sectional study to examine this association using the 2007 National Survey of Children's Health dataset (n = 77,951). We controlled for confounders and tested for autism-secondhand smoke interaction. Prevalence of asthma and autism were 14.5 % (n = 11,335) and 1.81 % (n = 1,412) respectively. Unadjusted odds ratio (OR) for asthma among autistic children was 1.35 (95 % CI 1.18-1.55). Adjusting for covari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 25 publications
4
40
0
Order By: Relevance
“…We found that children who are later diagnosed with ASD were not more likely than controls to be diagnosed with allergy, asthma, infections, autoimmune conditions, hematology, genitourinary, accidental injury, endocrine disorders or cardiovascular disorders in the years preceding ASD diagnosis. In contrast, some previous studies have reported that ASD is associated with comorbid medical conditions of allergies (Yaghmaie et al 2013; Theije et al 2014), asthma (Kotey et al 2014), infections (Atladottir et al 2010), autoimmune conditions (Gesundheit et al 2013), and endocrine disorders (Chen et al 2009). …”
Section: Discussionmentioning
confidence: 88%
“…We found that children who are later diagnosed with ASD were not more likely than controls to be diagnosed with allergy, asthma, infections, autoimmune conditions, hematology, genitourinary, accidental injury, endocrine disorders or cardiovascular disorders in the years preceding ASD diagnosis. In contrast, some previous studies have reported that ASD is associated with comorbid medical conditions of allergies (Yaghmaie et al 2013; Theije et al 2014), asthma (Kotey et al 2014), infections (Atladottir et al 2010), autoimmune conditions (Gesundheit et al 2013), and endocrine disorders (Chen et al 2009). …”
Section: Discussionmentioning
confidence: 88%
“…This was because the coexistence of asthma with complicated morbidities has a significant impact on the health outcomes of children. 33,34…”
Section: Settings and Participantsmentioning
confidence: 99%
“…Perhaps not surprisingly, levels of asthma, a disease associated with air pollution-induced inflammation [64-67], are substantially higher in children with ASD, consistent with common inflammatory mechanisms in lung and brain. In a nationally representative sample of 77,951 children, asthma was 35% more common in those with ASD after controlling for age, gender, body mass index, race, brain injury, secondhand smoke and socioeconomic status [68]; further the prevalence of both ASD and asthma has been increasing [69,70]. …”
Section: Introductionmentioning
confidence: 99%